Burn injuries in neonates admitted in Chittagong Medical College Hospital - Bhuiyan, Md Akbar Husain; Hoque, Md Momtazul; Chowdhury, Tanvir Kabir; Farooq, Abdullah Al; Sajid, Md Minhajuddin; Rahman, MA Mushfiqur; Banu, Tahmina (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: burn; neonate; scald; flame burn DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9109 JCMCTA 2011; 22(1): 28-31